Study on the Mechanical Properties and Failure Characteristics of Reinforced Segments Based on DIC - Xiao Li; Ou Geng; Qian Sun (预应力技术)
Shield tunnel segments are prone to damage in practical use and require reinforcement. In order to test the reinforcement effect of internal adhesive steel plates on the segments, bending static tests were conducted on the standard block segments of shield tunnels. The effects of different burial depths (divided into mid buried segments and ultradeep buried segments) and different initial damage levels (initial loading values of 78% of the failure load of mid buried segments and 90% of the failure load of ultradeep buried segments) on reinforced shield tunnel segments strengthened by steel plates were studied. The changes in the main strain and displacement field of the reinforced shield tunnel standard block segments were measured using the digital image correlation (DIC) method, and the failure characteristics (including strain and crack development laws) of the reinforced shield tunnel were studied. The test results show that there is no significant change in the principal strain of the mid buried pipe segment in the early and middle stages of the bending static test after using internal adhesive steel plates for reinforcement. However, after using steel plates of the same size for reinforcement of the ultradeep buried pipe segment, many cracks and stress increases are evident in the early and middle stages of loading. In the later stage of loading, the strain of both types of reinforced segments at the end of the steel plate will suddenly increase, and the cracks will extend diagonally toward the midspan direction. When the final damage occurs, the steel plate falls off, and the end of the steel plate used to reinforce the pipe segment becomes a weak point. When the bending moment changes from 500 kN to final failure, the displacement field of the buried pipe segment under initial loading to 78% of the failure load changes significantly, with the maximum value being 1.4 times the change in the ultradeep buried pipe segment under initial loading to 90% of the failure load. An internal adhesive steel plate can effectively improve the stiffness of the pipe segment and significantly reduce the displacement in both the X and Y directions of the pipe segment.